Herbicidal activity of pre and post emergent herbicide on control eleusine indica in aerobic rice system - Selvarajh, Gunavathy; Md Zain, Norhafizah; Seng, Chuah Tse; Aminudin, Anida (2018)
Aerobic rice system can be an alternate way to cultivate rice in less water conditions. However, weeds are a major constrain in aerobic rice field which decline its success. Weeds are being controlled by herbicides in aerobic rice but not all herbicides are effective in controlling various types of weeds. In this study, two pre-emergent (pretilachor and pendimethalin) and two post-emergent (cyhalofop-butyl and bispyribac-sodium) herbicides were evaluated for effective control of the bioassay species, Eleusine indica. It was found that pendimethalin at a higher application rate of 1.0 kg ai ha⁻¹ strongly inhibit the emergence and shoot growth of E. indica by >75% with negligible effect on the rice growth with stimulation on the leaf greenness. Conversely, pretilachor, cyhalofop-butyl and bispyribac-sodium gave moderate inhibition (55-60% inhibition) on weed emergence and shoot growth at higher application rates of 0.44, 0.1 and 0.035 kg ai ha⁻¹, respectively. Significant inhibitory effects on rice root growth were noticed at highest application rates of pretilachor, cyhalofop-butyl and bispyribac-sodium (40-50% inhibition) across the growth stage of rice seedlings. Great reduction in shoot height, shoot fresh weight, and greenness of rice plant also was evident at 0 DAS across herbicides rates. However, with increasing growth stages, the rice plant became less susceptible to the applied treatments. The finding suggested that pendimethalin at 1.0 kg ai ha⁻¹ was the most suitable application rate for inhibiting E. indica without injuring the rice seedlings.